Brasília e Washington: política externa divergente e as perspectivas da integração sul-americana - Silva, Ronaldo da (2010)
South America has become more distant in its relations with the United States and with the rest of Latin America in 2003-10. The social and economic failures of neoliberal policies led left-wing parties to seize power in most Latin American countries. The Free Trade Area of Americas (FTAA) was rejected. Brazil has been the main actor in pushing for the enlargement of MERCOSUR (incorporating Venezuela) and also for the integration of South America in a project named UNASUR Union of South American Nations (integration of infrastructure, plus economic and foreign policy). There are multiple forces for and against South American integration, in which Brasilia and Washington are sometimes rivals. Following the defeat of the FTAA, the United States engaged in deeper economic and military partnership with Colombia, Peru and Chile. As well as opposing views between Brasilia and Washington, there are old and new rivalries resurfacing among South American countries. The elites are ideologically susceptible to US power. South American integration/fragmentation (and the pivotal role of Brazil and the US) is important to geopolitics, foreign policy, trade and development in Brazil, and the whole region. This study seeks to understand the way Brasília and Washington cope with this new situation in which Brazil asserts its position as regional leader in South American integration and development. Circumstances have changed since the 20th century. In addition, other countries are pursuing their national interests.The goal of this study is to understand the important issues in economic integration. The issues include common infrastructure (eg trade, energy, transport) and political will/diplomacy, plus the divergent perspectives from Brasilia and Washington. Brazil as a rising power is more active and assertive in South America. The United States, for its turn, seeks to preserve the power it has enjoyed in the region. Today both countries are prone to a more tense dialogue. This study investigates integration and development from several perspectives using a variety of tools: socio and economic data, trade and historical analysis for diplomatic affairs between Brasilia and Washington DC and South American affairs. The perspectives of important foreign offices in the region are considered. Interviews with diplomats and scholars in international politics from several countries in the region were conducted in Brasília and Washington DC. This dissertation presents South American integration trends as influenced by Brazil and the US. It also describes Brazilian foreign relations and its ambitions with the subcontinent. There are four main result areas: (1) Regional integration launches Brazil in the world and may bring dividends to the economy and development of the region; (2) The US resists loss of their influence, launching several strategies; (3) There are enormous barriers and political, ideological and economic divergences to be overcome by the countries in regional integration; (4) The failure of the Doha Round of trade negotiations (WTO) favours regional integration among countries, in contrast to the global reach of trade and transnational companies.